ANALISIS PELAKSANAAN PENILAIAN OLEH GURU MATA PELAJARAN BIOLOGI SMA KELAS X DI KABUPATEN INDRAGIRI HULU - Evi Suryawati; R. Hussien Arief; Sepada Asmarika Kadir (Biogenesis, 2016)
ABSTRACT This study aimed to analyze the technical feasibility level assessments by teachers in implementing the evaluation of learning biology in the implementation of the curriculum in 2013, and to analyze the quality of items replay end of the semester the class X SMA Indragiri Hulu artificial 2014/2015 school year teachers based on difficulty level , distinguishing features and grains detractors. The research sample for analysis of the implementation of the assessment is taken as many as 10 schools that have implemented the curriculum in 2013 and incorporated in the MGMP. The research sample for analysis item which is about the end of the semester artificial replications 3 different groups of MGMPs biology. Data collected the primary data in the form of interview guidelines and documentation as well as secondary data in the form of questions and answer sheets replicates end of the semester. The data analysis technique used is descriptive analysis with percentages. Based on the results obtained penelititan that the level of feasibility assessment by subject teachers SMAN biology class X in Indragiri Hulu has not yet reached the National Education Standards. Assessment done by teachers is a written assessment by the average percentage of 100% with a very good category. Test questions difficulty level items Biology class X semester first semester SMAN in Indragiri Hulu TP 2014/2015 obtained an average 27.5% a matter of simple categories: average 47.5%: difficult 25%. For distinguishing items replay semester average gained about the ugly category of 29.2%: just 30%: 20% Good: excellent 8.3%: 12.5% negative. Item humbug (distractors) which serves good (D≥5%) gained an average of 13.3% while distractors were not functioning properly (D <5%) 86.7%. Key Words: Analysis Assessment , Lessons Biology , National Education Standards